Pioneering neurohackers: between egocentric human enhancement and altruistic sacrifice - Seyfried, Günter; Youssef, Sandra; Schmidt, Markus (Frontiers in Neuroscience, 2023)
The growing field of neurotechnology (NT) is becoming more and more accessible in terms of reduced costs, increasing availability and reliability of materials, and ways to implant devices. As in other engineering fields such as bio-or information technology, there is a growing community of pioneering hackers who (self-)experiment with NT and develop novel applications. While most debates about NT, its goals and ethical ramifications are usually conducted by professionals in the field (neuroscientists, −engineers, −ethicists), little is known within these institutional frameworks about the motivations, goals and visions of neurohackers and how they view ethical ramifications of NT therapeutics vs. human enhancement. In this study we draw on qualitative interviews with 13 of these neurohacking pioneers, who are interacting with NT from a grassroots perspective (i.e., a bottom-up and community/subculture-oriented approach), and shed light on: how they understand themselves in the context of human enhancement; what the role of invasive NTs is when it comes to identifying as a cyborg; if their practices show a clear distinction between therapy and enhancement; whether human enhancement is always about performance, optimization and functionality; and to which extent neurohackers contribute to “mainstreaming” NT.